Computational intelligence: engineering of hybrid systems - Negoita Mircea; Neagu Daniel; Palade Vasile (Berlin Springer-Verlag, 2005)
This book offers a gentle introduction to the engineering aspects of hybrid intelligent systems, also emphasizing the interrelation with the main intelligent technologies such as genetic algorithms ? evolutionary computation, neural networks, fuzzy syste
Keywords: Artificial intelligence; Computational intelligence